Association of Anthropometric and Body Adiposity Measures with Thyroid Dysfunction in Clinical Settings of Manipur, Northeast India - Baite, Kh Dimkhohoi; Lukram, Ajit; Baite, Jamkhoupum; Meitei, Sanjenbam Yaiphaba (Journal of Health and Allied Sciences NU, 2022)
Objective This study aimed to understand the association of anthropometric and body adiposity measures with thyroid dysfunction in clinical settings of Manipur, Northeast India.Materials and Methods The study included 160 Meitei and 152 Thadou-Kuki thyroid dysfunction patients undergoing treatment under medical specialists. Anthropometric data and related adiposity measures were collected along with the medical data.Results Hypothyroid represents 70.83% and hyperthyroid 29.17% of the total samples included in the study. The incidence of hypothyroid and hyperthyroid, irrespective of ethnic groups, is higher among females (87.49%) than males (12.49%). Hypothyroid individuals are significantly heavier and have higher adiposity measures than hyperthyroid, which is more significantly observed among the Thadou Kuki. Significantly higher waist circumference and weight to height ratio among the hypothyroid patients put the notion of adiposity deposition, apart from just water retention. Ethnic variation in the association reflects socioeconomic intervention in the management of thyroid problems.Conclusion In conclusion, proper dietary intake or supplements in the course of thyroid dysfunction treatment are important as they can complicate thyroid dysfunction patients with other associated comorbidities.
Keywords: hypothyroidism; hyperthyroidism; body adiposity; Meitei; Thadou Kuki